Optimal Conditions for Alkaline Delignification Process in Cellulose Isolation from Sengon Wood Sawdust - Intan Martha Cahyani; Adhyatmika; Endang Lukitaningsih; Teuku Nanda Saifullah Sulaiman (Science and Technology Indonesia, 2023)
Sengon wood sawdust (SWS) is a solid waste of the wood industry with the potential as a source of cellulose and can increase its economic value. However, cellulose in plants is tightly bound to lignin which is called lignocellulose therefore needs to be delignified before utilization. In this study, we determined the optimum conditions for delignification from sengon wood sawdust cellulose (SWSC). Optimization variables were determined with the parameter of obtained hemicellulose, cellulose, and lignin content. The optimization of SWSC delignification was then carried out using the factorial design by analyzing the effect of sodium hydroxide (NaOH) concentration (2% - 10%) and ratio (SWS : NaOH solution) (1:10 â€“ 1:80) on hemicellulose, cellulose, and lignin content. Optimal conditions were obtained at 2% NaOH (1:19.20) with concentrations of 8.01% hemicellulose, 52.49% cellulose, and 22.2% lignin. One sample T-test analysis of predictive and research values of hemicellulose, cellulose, and lignin showed insignificant results (P>0.05) which means that the optimization equation proved valid to determine the optimum conditions for cellulose delignification of sengon wood sawdust. FT-IR analysis, SEM imaging, and particle size distribution (PSA profile) showed that the cellulose produced under these conditions has similar characteristics to the standard of AvicelÂ® PH 102.